Creped Tissue Paper: A Microarchitected Fibrous Network. Issue 2 (15th October 2020) - Das, Ratul; Pan, Kui; Green, Sheldon; Phani, A. Srikantha
Abstract : Tissue paper is a thin complex nonlinear fibrous material made from fiber layers thinner (≈100 μm) than a human hair. Though it appears as a slender two‐dimensional material to our eyes, its internal microstructure reveals an intricate architected fibrous network of only 1–5 wood fibers within its thickness. The fiber network is folded in one direction giving rise to a characteristic crepe structure. Using high‐speed imaging, the crepe structure is shown to emerge from a dynamic, coupled mechanical deformation processes of fracture and buckling, occurring on a length scale of few hundred micrometer. Bending and stretching of the folds at the macroscale of the paper and at the microscale of the individual fibers are shown to govern the material's tensile properties, including the strain to rupture and the elastic modulus. Insights from this study can guide the development of strong, soft fibrous materials for biomedical and consumer products. Abstract : Creped tissue paper is widely used for health and hygiene, but least studied despite its extreme material properties. Herein, it is revealed that how a folded internal structure in this slender material emerges in its manufacturing process, and governs its extreme flexibility and softness. Understanding and controlling the folds can guide the design of architected fibrous networks for biomedical and consumer product applications.